Pendampingan Literasi Digital Bermedia Bagi Remaja di Desa Pesisir Pangandaran - Maryam Erlina; Lia Muliana; Nuryamujiatun (CV. Biha Cendekia, 2025)
The rapid development of digital technology has significantly influenced the information access patterns of teenagers, including those in coastal areas such as Babakan Village, Pangandaran District. Low levels of digital literacy make adolescents vulnerable to exposure and the spread of hoaxes and negative content. This community service research aims to improve teenagers’ critical and ethical digital media literacy skills through a participatory-based mentoring program. This study employed a descriptive qualitative approach consisting of four stages: needs assessment, socialization and training, digital media mentoring, and activity evaluation. Data were collected through observation, interviews, documentation, and post-tests. The results showed an increase in digital literacy by 38%, from an average score of 56 to 94. A total of 85% of participants were able to verify information before sharing, and 80% successfully produced educational digital content published on social media. This activity demonstrates that contextual and community-based digital media literacy mentoring effectively builds ethical awareness, critical skills, and a positive digital ecosystem in coastal villages.